Application of slag cement based aerated lightweight concrete in non-load bearing wall panels - 197752 Arresh Vhina Narayanan (Skudai : Universiti Teknologi Malaysia, 2002)
Thesis (Master of Engineering (Structure and Material)) - Universiti Teknologi Malaysia, 2002